Advanced Glycation End Products, a Potential Link between Psoriasis and Cardiovascular Disease: A Case-control Study - (:unkn) unknown (WOLTERS KLUWER MEDKNOW PUBLICATIONS, 2019)
Context: Advanced glycation end products (AGEs) promote oxidative stress and inflammation by altering structure and function of proteins. They are excessively produced mainly in hyperglycemia, chronic inflammation and are involved in the development of atherosclerosis and cardiovascular disease. Aims: The aim of this study was to investigate whether skin AGEs levels were increased and had relation to premature atherosclerosis in patients with psoriasis. Subjects and Methods: Fifty-two psoriasis patients and 20 healthy controls (HC) were included. AGEs were determined by skin autofluorescence (SAF) analysis. High-sensitive C-reactive protein (hsCRP) and carotid intima-media thickness (CIMT) were also investigated. Physical activity and dietary patterns were determined. Statistical Analysis Used: Fisher's exact test, two-sample t-tests, MannuWhitney-U test, Pearson correlation, Spearman correlation, and Wilcoxon test. Results: SAFs were increased in psoriasis patients (1.8 arbitrary units [AUs]) compared to that in HC (1.6 AUs) (P = 0.057). Median CIMT values of HC and psoriasis groups were 0.43 (0.28-0.79), and 0.59 (0.44-0.98) respectively and the differences were significant (P = 0.001); hsCRP levels were not different between groups. Conclusions: Skin AGE accumulation was found to have a correlation with CIMT in psoriasis patients providing evidence for the role of AGEs in premature atherosclerosis.
Keywords: Advanced glycation end-products; atherosclerosis; cardiovascular morbidity; carotid intima-media thickness; psoriasis; SKIN AUTOFLUORESCENCE; MYOCARDIAL-INFARCTION; DIABETIC-PATIENTS; RISK; INFLAMMATION; ARTHRITIS; GLYCOXIDATION; METHOTREXATE; INHIBITORS; MORTALITY